PAKET PENDIDIKAN KESEHATAN UNTUK MENINGKATKAN KESIAPAN IBU HAMIL RESIKO TINGGI DALAM MENGHADAPI PERSALINAN - Oktafia, Riski; Setyowati, Setyowati; Gayatri, Dewi (Indonesian Journal of Nursing Health Science, 2018)
WHO estimates that 800 women has died because of pregnancy complication and delivery process everyday. Approximately 80% maternal mortality in the world is caused by the complication during pregnancy, delivery and postpartum.Those situation needs a comprehensive health education to prepare the high risk pregnant women. The aim of this study is to identify the influence between package health education to prepare the high risk pregnant women in delivery. This research used a quasy experiment involved 43 sample. The birth preparedness and complication readiness (BPCR) is used in this study. The result showed that there is an influence of p package health education to prepare the high risk pregnant women in delivery (p=0,001). This study recommend that it is important to used this package in the health education for high risk pregnant women. Â Keywords: high risk pregrancy, birth preparedness, health education